Pornografia de vingança e violência de gênero: uma análise sobre a aplicabilidade da criminalização como medida de tutela dos direitos sexuais femininos - NUNES, Ana Carolina Endres (2020)
In the past few years, with the advent of the Internet and social networks, there has been a staggering growth in cases of intimate content sharing, with sexual or erotic connotations without the consent of victims, which demands the attention of the judiciary and law enforcement. In this paper, after a brief explanation about the conceptions of gender, we intend to delimit the contours of the so-called revenge pornography, analyzing its origin, history, thermology and real cases, reaching the conclusion that it is a new modality of gender violence against women. It is also analized how the country's criminal justice system dealt with the issue prior to its typification, listing laws related to the theme, and then analyzing the specific type brought by Law 13,718 / 18. Lastly, there are critics about the criminalization, as it is understood that the handling of the problem by the criminal justice system is insufficient to prevent and repress new occurrences. Therefore, alternative methods to criminalization are presented in order to show other ways to combat this crime, which act directly on its causes and effects.